Pemberdayaan Ekonomi: Pelatihan Kewirausahaan dan Keterampilan untuk Masyarakat Pedesaan - Mannahali, Misnah; Asri, Wahyu Kurniati; Fatimah, Syarifah; Azizah, Laelah; Angreany, Femmy (Program Studi Manajemen FEB UNM, 2024)
Entrepreneurship and skills training for rural communities in Anggeraja District has successfully improved the skills, knowledge, and economic independence of participants. This program focuses on developing technical skills relevant to local potential, such as handicrafts and modern agriculture, as well as providing an understanding of basic entrepreneurship and marketing through digital technology. The results of this training show improvements in product quality, competitiveness, and the application of technology in small businesses. Additionally, the formation of strong social networks among participants has further strengthened community solidarity and provided support for business development. However, challenges related to access to finance and technological infrastructure still remain as barriers that need to be addressed to expand the program’s impact. Therefore, for sustainability and broader impact, increased access to technology, ongoing mentorship, and easier access to finance, as well as collaboration with relevant stakeholders, are needed to support entrepreneurship development in rural areas.